2016
DOI: 10.1111/codi.13518
|View full text |Cite
|
Sign up to set email alerts
|

Repair of transperineal recto‐urethral fistula using a fibrin sealant haemostatic patch

Abstract: Direct transperineal repair of RUF reinforced with a fibrin haemostatic patch of TachoSil is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A number of biomaterials have been evaluated as potential treatments of noncompressible hemorrhage. Scientists have long sought to harness the clotting power of fibrin to create hemostatic dressings or bandages . Fibrin‐based hemostatic sealants were first investigated in the 1940s and proved to be quite useful .…”
Section: Introductionmentioning
confidence: 99%
“…A number of biomaterials have been evaluated as potential treatments of noncompressible hemorrhage. Scientists have long sought to harness the clotting power of fibrin to create hemostatic dressings or bandages . Fibrin‐based hemostatic sealants were first investigated in the 1940s and proved to be quite useful .…”
Section: Introductionmentioning
confidence: 99%
“…In one series, Giuliani et al demonstrated successful closure of rectourethral fistulas in four of five patients when Tachosil® was used. 15 Giusti et al successfully utilized Tachosil® as an interposition tissue in a series of 16 laparoscopic extravesical vesicovaginal fistula repairs. 16 However, the relative contribution of Tachosil to the success of the repair is unknown, and therefore its utility in UCF repairs remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of bioactive materials is a promising pathway to improve the performance of PEO-based nanofibers, and the use of clotting power of fibrin to create hemostatic dressings can be quite useful. , In this sense, the loading of thrombin inside PEO nanofibers increases their bioactive potential, resulting in a dressing with faster blood clotting capacity. Polymer–protein conjugates are able to form complex molecules with particular interest in the fields of biomedicine .…”
Section: Introductionmentioning
confidence: 99%